Structural and solvent dependence on the molecular and nonlinear optical properties of 10-octyl thiophene-based phenothiazine and substituted derivatives – a theoretical approach - Oluwatoba Emmanuel Oyeneyin (Journal of Taibah University for Science, 2018)
This work presents an investigation on the structural and solvent dependence on the molecular, electronic and nonlinear optical properties of some conjugated organic molecules based on phenothiazine units using quantum chemical calculations with pure BLYP and hybrid B3LYP correlation with a high polar basis set, 6–31G* in the gas-phase and in solutions towards understanding their structure–property relationship. The ground state molecular properties like the frontier orbitals (FMOs) energies, dipole moments (μ), polarizabilities (α), molecular first hyperpolarizabilities (β) were obtained. The results showed that the insertion of substituents enhanced molecular properties like the optical limiting abilities. It was also observed that the energy band gap (Eg), derived from the FMOs were reduced while μ, α and β increased. The λmax of the substituted derivatives are higher than the unsubstituted 10-octyl thiophene-based phenothiazine and results obtained are in good agreement with available experimental findings. The substituted derivatives proved to possess better optical responses than the unsubstituted derivative on the basis of the properties analysed.